Phase field simulation for recrystallization kinetics of cold-drawn 0.12wt%C steel in full annealing (2014)
The importance of recrystallization kinetics in metal process cannot be over emphasized in providing information as to the control of microstructure of materials for purpose of improving or impacting desired mechanical properties in processed materials. In this study, 0.12wt% C steel cold drawn between 20% - 55% were graduallyheateduptoatemperatureof900°C followed bysoakingtreatment between 600 seconds and 3600 seconds in a Gallenkomp® mufflefurnace model SVL-1009 with voltage regulation of 220 V, 50 Hz of temperature range 300°C - 1000°C. The influence of the annealing process on the strength and impact toughness properties of the annealed steel were evaluated from tensile and charpy-impact tests conducted on the annealed steel. A phase field method is used to describe the recrystallization kinetics of the annealed cold drawn 0.12wt%C steel for the different degrees of cold drawn deformation. The experimental data obtained from the tensile and charpy-impact test were used as input data for the phase field simulation of the recrystallization process. The results show that the yield strength of the annealed cold drawn 0.12wt% C steel increases with increasing soaking time within the range of 600 sec.– 3600 sec. for the 20% cold drawn steel, between 600 sec.- 2400 sec. for the 25% and between 600 sec.-1800 sec. for the 40% and 55% cold drawn steel. The treatment increased the impact toughness of the steel for the 20%-40% cold drawn deformation but loses its toughness for the 55% cold drawn steel. The tensile strength however reduces for all the cold drawn steel irrespective of the degree of deformation. The simulation results show that reformation of grains in cold drawn 0.12wt%C steel depends on the degree of cold drawn deformation and the soaking time of annealing. The response of the mechanical properties of the annealed cold drawn 0.12wt% C steel therefore depends on the degree of cold deformation and soaking time of annealing